1995
DOI: 10.1159/000217952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gonadal Steroids on the Growth of Human Pituitary Adenomas in vitro

Abstract: The effects of testosterone (T), dihydrotestosterone (DHT) and methyltrienolone (R 1881) on cell proliferation of eight human pituitary tumors in culture wre assessed by [3H]thy-midine incorporation and compared to those of progesterone (Pg) and 17β-estradiol. Receptors for androgens (AR), estrogens (ER) and progesterone (PgR) were characterized. AR had a significant inhibitory effect on all AR-positive tumors, whatever their hormonal content. Inhibitory effects of either T and DHT < R1881 < Pg were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…With respect to pituitary tumors, our study expanded upon the limited, published data referred to in the introduction [16][17][18][19]. We found gonadotroph and null cell and corticotroph adenomas to show higher frequencies of AR positivity than did other adenoma types.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…With respect to pituitary tumors, our study expanded upon the limited, published data referred to in the introduction [16][17][18][19]. We found gonadotroph and null cell and corticotroph adenomas to show higher frequencies of AR positivity than did other adenoma types.…”
Section: Discussionmentioning
confidence: 80%
“…6 Corticotroph adenoma. Note the AR immunoreactivity in this rather frequently immunoreactive adenoma variant Nonetheless, in vitro effects of androgens upon adenoma cell growth have been studied in a serum-free medium [18]; the authors demonstrated enhanced growth of both gonadotroph and prolactin cell adenomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from our laboratory have shown that PA express sex steroid hormones receptors with a differential pattern according to phenotype and patient's gender and gonadal function (Jaffrain-Rea et al 1996 ) , and that sex steroids are able to modulate their proliferation in vitro accordingly (Caronti et al 1995 ) . In particular, ER expression was higher in male prolactinomas and 17 b -estradiol had a proliferative effect on most ER-expressing PA.…”
Section: Ahr and Endocrine Disruptionmentioning
confidence: 99%
“…The intensity of fluorescence of the sample was compared to an intensity scale obtained by serial dilutions of a goat anti-mouse IgG F(ab),-FITC. In order to verify whether increased elastin production by pathological fibroblasts could result from enhanced cell proliferation, in vitro [3H]-thymidine incorporation by both normal and pathological cells was evaluated at days 1, 2, 3, 6 of culture in complete medium, as previously described (23). The test was carried out in triplicate on each culture and results were expressed as mean count per minute (mean c.p.m.).…”
Section: Skin Biopsies and Cell Culturesmentioning
confidence: 99%